Predictors of Response to Biologics in Patients with Moderate-to-severe Psoriasis: A Danish Nationwide Cohort Study - Christopher Willy Schwarz; Nikolai Loft; Mads Kirchheiner Rasmussen; Christoffer V. Nissen; Tomas Norman Dam; Kawa Khaled Ajgeiy; Alexander Egeberg; Lone Skov (Medical Journals Sweden, 2021)
Identifying patient characteristics associated with achieving treatment response to biologics in patients with psoriasis could prevent expensive switching between biologics. The aim of this study was to identify patient characteristics that predict the efficacy of treatment for biologics that inhibit tumour necrosis factor-α, interleukin-12/-23, and -17A. The study investigated biologic-naïve patients from the DERMBIO registry treated with adalimumab, etanercept, infliximab, secukinumab, or ustekinumab. Multivariable logistic models were conducted to assess associations between patient characteristics and treatment response. A total of 2,384 patients were included (adalimumab n = 911; etanercept n = 327; infliximab n = 152; secukinumab n = 323; ustekinumab n = 671). Smoking (odds ratio 0.74; 95% confidence interval (CI) 0.56-0.97; p = 0.03) and higher bodyweight (odds ratio 0.989; 95% CI 0.984-0.994; p < 0.001) reduced the odds of achieving response defined as Psoriasis Area and Severity Index ≤2.0 after 6 months of treatment. In conclusion, higher bodyweight and smoking were associated with a reduced probability of treatment response for tumour necrosis factor-α inhibitors, ustekinumab, and secukinumab.